Stories of Our Fellow Mathematics Tutors during Covid-19 Pandemic - Taqiyuddin, Muhammad; Firdausi, Faliqul Jannah; Asidin, Mohamad Tri Afriyadi Nur (IndoMath: Indonesia Mathematics Education, 2022)
The tutoring phenomenon has been discussed from multiple angles. Sometimes, math tutors, as part of the tutoring system, are framed as the contributors of shadow education and the parasite of the national educational system. We claim that some math tutors are financially vulnerable. Our paper serves to bring new nuances into the complexity of being math tutors during the Covid-19 pandemic time. In doing so, we employed the qualitative study method by elaboratively interviewing five Indonesian mathematics tutors during September 2021. Specifically, this article focused on three aspects related to math tutoring: challenges, adaptations, and success. By listening to their stories, we gained some insights. First, tutors who were struggling the most are the ones who come from a poor background and who work for middle-low-income students. Second, the cost of adapting to the new work environment as math tutors need to upgrade their devices is one of the contributing factors in transitioning from offline tutoring to online tutoring. Third, those who thrived are the ones who are familiar with online tutoring, already have decent devices which are sufficient for heavy online multi-tasking work, and are in the circle of upper-middle-income families. In retrospect, this research not only sheds light on social issues in our educational system but also raised some key practical issues of teaching mathematics online which may affect tutors with various backgrounds differently. All in all, our research is part of our endeavor to fight for math tutors’ welfare.